KONSEP PENDIDIKAN BERBASIS KETELADANAN (USWAH HASANAH) DALAM HADIS TARBAWI DAN IMPLEMENTASINYA DI ERA DIGITAL - Riki Adi Pratama; Sunita, Wiwin; Ghani, Ainal; Cahaya Kesuma, Guntur; Amirudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the concept of character-based education through the principle of uswah hasanah (good example) in Hadith Tarbawi and its implementation in the digital era. The problem addressed is the moral crisis and the weakening of exemplary values in modern digital-based education. The purpose of this study is to analyze selected prophetic traditions linguistically and contextually and to formulate practical strategies for implementing exemplary-based Islamic education in digital environments. This research employs a qualitative library research method using classical hadith sources and contemporary educational literature published within the last eight years. The findings indicate that the prophetic traditions emphasize two fundamental principles: the integration of learning and teaching (khayrukum man ta‘allama al-Qur’an wa ‘allamahu) and consistency in good deeds (adwamuha wa in qalla). These principles remain highly relevant in digital education through ethical online conduct, consistent value transmission, and authentic digital content creation. The study concludes that digital media should function as a strategic platform for expanding prophetic exemplary education.